Dinamika Peruntukkan Lahan Kawasan Gumuk Pasir Parangtritis Berdasarkan Citra Satelit - Dwi Kunto Nurkukuh; Candra Ragil (Retii, 2021)
A sand dune is a sand mound formed by sand blown by the wind. One of the unique sand dunes found in the Special Region of Yogyakarta, in fact it is the only sand dune in Southeast Asia. The sand dune is located in Parangtritis Village, Kretek District, Bantul Regency, which is a geoheritage area. As the Parangtritis sand dune is an area that needs to be protected and preserved, it is necessary to take steps to keep the sand dune alive. Changes in land use often occur in several areas. There are concerns that a similar incident could occur in the sand dune area which could adversely affect the loss of the sand dune. Therefore, it is necessary to conduct research on the dynamics of land use in the Gumuk Pasir Parangtritis area. This research method uses a qualitative approach with document inspection techniques in the form of satellite images. Analysis technique through satellite image classification in ArcGIS software. Analysis of satellite image classification is a grouping of color hues in satellite images according to the degree of similarity. Looking at the satellite image of the Parangtritis sand dune area, it is found that the land use classes are: Sand Dunes, Vegetation, Buildings, Wetlands, Dry Land, and Water. Observations of satellite imagery were carried out in 2010-2020 through Google Earth. This research produces a dynamic map of the land use of the Gumuk Pasir area for 2010, 2015, and 2020. From the map it can be found that during 2010-2020 that sand dunes decreased by 21.36 ha, vegetation decreased by 47.04 ha, buildings increased by 62.3 ha, wetlands decreased by 34.63 ha, dry lands increased by 45.95 ha, and water increased by 0.07 ha.